Data mining and content analysis of the jury citations of the Pritzker Architecture prize (1977–2017) - Mahdavinejad, Mohammadjavad; Hosseini, Seyed Amir (Journal of Architecture and Urbanism, 2019)
Although the Pritzker Architecture Prize is prestigious and highly influential, it has not been the subject of any coherent studies to date. This research investigates the network of sponsors, the jury members influential on the nomination process, as well as the discourses dominant during each year of the prize. In the first section, we examine the network of sponsors using the bibliography method. In the second section, we study the contents of the annual jury citations using the content analysis method. The second section shows that each announcement contains four parts and various sub-parts. we compare the results of both sections to draw a content map of the various years of the prize. Finally, we attempted to evaluate the relationship between the jury members and their cooperation network with the discourses formed over time.